IMPLEMENTING ER FOR VOCATIONAL HIGH SCHOOL STUDENTS THROUGH LITERACY CLOUD - verina, nanin (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
This paper reports on the implementation of an Extensive Reading (ER) program using Literacy Cloud for mobile English learning, and the perception of the student participants. For roughly four weeks, 45 EFL students enrolled in third grade from two major courses, namely a pharmacy and dental assistant course at a vocational high school in East Java, Indonesia, joined this program to experience extensive reading through Literacy Cloud for mobile English learning. They had no experience to use Literacy Cloud before, so literacy cloud is introduced to support ER program. Data was gathered with a questionnaire and interviews were given to ascertain student experience using Literacy Cloud in ER class. The results show that students had positive attitudes and perceptions about Literacy Cloud and felt that Literacy Cloud was very useful for supporting the development of their English skills, especially their reading skill. The results of this study have implications for English language teaching, for deploying ER with vocational school students. The integration of technology such as Literacy Cloud can provide many benefits for the students’ reading skill development.